A Japanese case of lymphocytic esophagitis. Issue 4 (22nd December 2015) - Maejima, Ryuhei; Uno, Kaname; Iijima, Katsunori; Fujishima, Fumiyoshi; Noguchi, Tetsuya; Ara, Nobuyuki; Asano, Naoki; Koike, Tomoyuki; Imatani, Akira; Shimosegawa, Tooru
Abstract : We report the case of a 68‐year‐old Japanese man diagnosed with lymphocytic esophagitis (LE), a rare disease associated with refractory dysphagia. He has had severe dysphagia and heartburn since 2007. Findings of esophagogastroduodenoscopy (EGD) carried out by a local physician in 2010 showed pale mucosa with white exudate and lateral furrows in the esophagus. He was referred to Tohoku University Hospital in 2012, because the symptoms did not improve, despite regular use of a proton pump inhibitor (PPI). At that time, EGD revealed the coexistence of a slight stricture in the upper esophagus, the histopathological findings of which included a predominantly peri‐papillary distribution of abundant, infiltrating CD3 + /CD4 + /CD8 + /CD20 − lymphocytes without any granulocytes (CD4 +  : CD8 +  = 3.3:1). These were consistent with a diagnostic criteria of LE. Thereafter, severe dysphagia with food impaction occurred twice a month, despite the long‐term use of a PPI, and EGD showed worsened strictures, where endoscopic ultrasonography findings showed marked circumferential thickness of the mucosal and submucosal layers. Then, one session of endoscopic balloon dilatation dramatically improved the dysphagia. Accordingly, LE should be considered an important differential diagnosis of refractory dysphagia based on the characteristic features of endoscopic and pathological findings.